Insights into free radical and non-radical routes regulation for water cleanup - Yi Zhou; Wenxuan Guo; Yanpan Li; Ming Gao; Xuning Li; Wenyuan Liu; Zhuan Chen; Xiaohui Zhang; Yanbo Zhou; Mingyang Xing (Nature Communications)
Abstract In the field of wastewater treatment, the regulation of free radical and non-radical routes has been one of the major challenges. This study investigates the regulation of radical and non-radical oxidation pathways in the peroxymonosulfate (PMS) oxidation system by controlling the calcination temperature of carbon materials and constructing bimetallic single-atom catalysts (NC-FeMn(TA)). Density functional theory calculations and experimental tests indicate that increasing the pyridinic nitrogen content and incorporating single metal atoms in nitrogen-doped carbon materials result in a predominantly non-radical oxidation process. In contrast, enhancing the content of graphitic and pyrrolic nitrogen species and introducing bimetallic catalytic centers promote a radical oxidation pathway. The NC-FeMn(TA)/PMS system demonstrates high oxidation performance over a broad pH range, exhibiting significant interference resistance and stability, with 100% degradation of target pollutants after 22 cycles and complete removal of emerging pollutants (including pharmaceuticals and personal care products, endocrine disrupting chemicals, dyes and chemical materials) within 5 min. This system’s remarkable performance suggests broad application potential in water pollution control field.